Analisis Kinerja Keuangan Pt. Weha Transportasi Indonesia Tbk. Pada Saat Dan Setelah Pandemi Covid-19 - Firdayanti Firdayanti; Niar Astaginy; Agus Zul Bay (Student Scientific Creativity Journal, 2023)
This study aims to determine: the level of success of the financial performance of PT Weha Transportatio Indonesia Tbk. During and After the Covid-19 Pandemic in 2020, 2021 and 2022. Judging from the analysis of financial ratios. This research uses quantitative methods with a descriptive approach. The data collection technique used in this research is library research. The population of this study are all financial statements of PT Weha Transportation Indonesia Tbk. 2020, 2021 and 2022. While the sample of financial statements in the form of balance sheets and income statements from 2020, 2021, 2022. The data analysis method used in this research is descriptive quantitative and financial ratio testing which includes liquidity ratios, solvency ratios, profitability ratios, and activity ratios. The results showed that the financial performance of the company PT Weha Transportation indonesia Tbk. Experienced a decline in 2020, namely when the Covid-19 pandemic occurred, and the financial performance of transportation companies before Covid-19 was better than during the Covid-19 pandemic. And experienced an increase after Covid-19.